An enhanced CLSVOF method with an algebraic second-reconstruction step for simulating incompressible two-phase flows. (September 2022) - Meng, Wenkang; Liao, Lei; Chen, Min; Yu, Ching-hao; Li, Jia; An, Ruidong
Highlights: A new coupling scheme for coupled level set and volume of fluid (CLSVOF) method was put forward. An algebraic second-reconstruction step was introduced for obtaining accurate interface parameters. Several benchmark tests were carried out to prove the superiority of the proposed method. Simulations of dam-break flows with violent free surface deformation were carried out. Abstract: The CLSVOF (coupled level set method and volume of fluid) method is a widely-used approach for capturing interfaces in engineering applications of computational fluid dynamics (CFD) due to its accurate interface computation, small mass error and ease of extension to 3D (three-dimensional) simulations. To further enhance this method, a second-reconstruction CLSVOF method is used to simulate incompressible two-phase flows issues with high surface tension effects or not. In the proposed improved method, an algebraic second-reconstruction step is introduced and will be performed after the re-initialization step of the standard CLSVOF process, aiming at obtaining accurate two-phase flow interface parameters. The proposed method introduces a new interface function by means of a sigmoid formula, based on the ultimate LS function calculated by the standard CLSVOF steps. In order to evaluate the superiority of the proposed method compared to existing methods, several benchmark tests are carried out, including two-dimensional rising bubble, three-dimensional rising bubble, two-dimensional dam-break flow with a wet bed, and three-dimensional dam-break flow with an obstacle. The results show that the proposed method is more accurate than existing methods, while guaranteeing almost no mass error. In addition, the simulated results of the air-water interface agree well with those in previous experiments data.